2019
DOI: 10.2147/ndt.s196541
|View full text |Cite
|
Sign up to set email alerts
|

<p>Overcoming barriers to effective management of tardive dyskinesia</p>

Abstract: Tardive dyskinesia (TD) is a heterogeneous syndrome of involuntary hyperkinetic movements that is often persistent and occurs belatedly during treatment with antipsychotics. Recent approval of two dopamine-depleting analogs of tetrabenazine based on randomized controlled trials offers an evidence-based therapeutic approach to TD for the first time. These agents are optimally used within the context of a comprehensive approach to patient management that includes a practical screening and monitoring program, sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 96 publications
(102 reference statements)
0
36
0
3
Order By: Relevance
“…Prevention remains the best strategy to treat TD. Screening tests and the frequency of their taking, the doses and duration of using the drug play a key role in the early diagnosis and thus the prevention of TD [10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Prevention remains the best strategy to treat TD. Screening tests and the frequency of their taking, the doses and duration of using the drug play a key role in the early diagnosis and thus the prevention of TD [10].…”
Section: Discussionmentioning
confidence: 99%
“…Rigorous trials have confirmed that both drugs are more effective than placebo in reducing the severity of TD and are better tolerated than tetrabenazine [9]. Caroff in his study showed that the use of valbenazine reduces the symptoms of TD, even 4 weeks after its discontinuation [10].…”
Section: Tetrabenazine Analogsmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of well-being during pharmacotherapy is receiving more and more attention [129] and is particularly relevant in explaining the high adherence of some patients to clozapine, demonstrated by the lower discontinuation rates in cohort studies [127,128]. Clozapine positive effects on well-being in some patients may be influenced by clozapine effects on extrapyramidal symptoms [130][131][132][133][134][135][136][137][138][139][140][141][142], hostility [143,144] and the "awakening" phenomenon [145][146][147] (online suppl. Box S5, section 3).…”
Section: Clozapine and Well-beingmentioning
confidence: 99%